Hadiths About Marriage in Legal Reasoning Judges of Religious Courts in West Sumatra: Living Hadith Studies - Yusrizal Efendi; Hafizzullah Hafizzullah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This study aims to clarify and examine the pattern of the hadith narrations regarding marriage that are cited, authenticated, and validated in the legal reasoning of religious court judges' rulings. This study is a library study that takes the form of a written living hadith. By using the takhrij al-hadith approach, the hadith's veracity is confirmed, and its applicability is assessed using the perspectives and techniques of hadith experts. Inductive techniques are then used to process the outcomes. Two methods of citing hadith history were discovered via the research: using a template application and directly citing the hadith book. Only five of the 22 cases in the subfield of marriage, including marital dispensation, wali 'adhal, divorce, determining the parentage of the kid and determining the child's adoption, and Itsbat of marriage, include hadith citations. The five examples pertain to seven hadith histories that fit the criteria for Prophet Saw's hadiths. Four are fully cited with sanad and rawi, two are only stated with sanads that differ from rawi, and one is quoted without sanad and rawi (divorce case). Although it does not have legal implications that lead to the annulment of the judge's decision, the condition of the absence of quoting hadith as one of the legal considerations in copies of the decisions of cases shows the lack of authority of decisions that characterize Religious Courts.